Analisis Kualitatif terhadap Faktor-Faktor yang Mempengaruhi Motivasi Belajar Siswa Kelas X SMAN 1 Cigudeg : Kajian Literatur - Mochamad Rizki (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to analyze the factors influencing the learning motivation of Grade X students at SMAN 1 Cigudeg. A qualitative approach with a literature review method was used, gathering data from relevant secondary sources. Based on the analysis of literature, it was found that internal factors such as Self-efficacy and interest play an important role in student motivation, while external factors such as the role of teachers, paren al support, and the learning environment have a greater impact. The use of technology and social interaction also influence students' motivation. The study’s findings show that external factors have the largest contribution to students' learning motivation. This research is expected to provide deeper insights into student motivation in secondary education.